The cyprus puzzle and the Greek - Turkish arms race: Forecasting developments using genetically evolved fuzzy cognitive maps - Zombanakis, G. A.; Andreou, Andreas S.; Mateou, N. H. (My University, 2003)
The scope of this paper is to forecast the extent to which a settlement of the Cyprus issue may be possible given the decisions taken during the Copenhagen EU summit. It aims, in addition, at investigating the possibilities of improvement in Greek-Turkish relations which may lead, in turn, to reducing the arms race between the two countries. The paper uses a Genetically Evolved Certainty Neuron Fuzzy Cognitive Map algorithm to consider a number of scenarios examining the possible reactions of all sides involved in the Cyprus issue, namely Greece, Turkey, Cyprus, the Turkish-Cypriot community and the international environment. All simulation exercises suggest that the Greek and the Cypriot side should not necessarily rely on the decisions taken during the Copenhagen summit conference. The forecasts point out, in addition, that the optimism of the Greek government concerning the outlook of its relations with Turkey, and a subsequent reduction of the arms race against it, is far from being justified.
Keywords: Arms race; Fuzzy cognitive maps; Genetic algorithms; Hybrid modelling